Konsep Self-Healing dalam Al-Qur’an: Studi Kitab Tafsir Al-Azhar Karya HAMKA Q.S Al-Baqarah Ayat 45 dan 153 - Hazmi, M. Hafiz Mauluddin; Bashori, Bashori (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2025)
Generation Z is often perceived as having weak mental resilience, with high rates of mental health issues among adolescents. The I-NAMHS 2022 report indicates that one in three teenagers experiences mental health disorders, and 59.1% of Generation Z feels distressed. The primary causes include excessive technology use, stress, sedentary lifestyles, social pressure, and high expectations. Effective solutions, such as self-healing, are crucial for calming oneself, reducing stress, and enhancing comfort to improve mental health. This article discusses the concept of self-healing from an Al-Qur'an perspective through Q.S. Al-Baqarah verses 45 and 153, emphasizing prayer (salat) and patience (sabar) as means to achieve inner peace and strengthen the soul. This study employs library research with a qualitative-descriptive approach to analyze the concept of self-healing in the Al-Qur'an. Primary sources include the Al-Qur'an and Tafsir Al-Azhar by HAMKA, while secondary sources comprise relevant books and journal articles. The research findings demonstrate that in addressing mental health issues, particularly among Generation Z, the self-healing concept taught in Q.S. Al-Baqarah verses 45 and 153 is highly relevant. These verses teach the importance of patience and prayer in strengthening the soul, overcoming emotional burdens, and achieving inner tranquility. By applying the values of forgiveness, gratitude, self-compassion, and mindfulness through prayer and patience, individuals can enhance their mental well-being, face life's pressures with greater calm, and strengthen their emotional resilience.